Effectiveness of Cooperative Script Learning Method on Students' Collaboration Skills - Shofia Salma Azzahro; Hamam Burhanuddin; Ida Fauziyatin Nisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article discusses the effectiveness of the Cooperative script learning method on student collaboration skills in class X Aqidah akhlak subjects at MAN 2 Bojonegoro. This study is motivated by MAN 2 Bojonegoro school which is still using conventional methods such as lectures, questions and answers and writing. Therefore students are sleepy and unfocused, this factor is the basis for applying the Cooperative script learning method with collaboration skills. This learning activity is assumed to be on the principles of learning that can only be done when all students are active in learning activities in groups, with the teacher's role only as a facilitator. The approach taken in this research is a quantitative approach. With the type of experimental research. Based on the results of the research that has been conducted, the following results were obtained: (1) that the use of Cooperative Script learning method affects students' collaboration skills. (2) The advantage in applying the Cooperative Script learning method is that it makes students active in learning.